Indicadores de qualidade física em latossolos cultivados com milho e soja sob semeadura direta e cultivo convencional - Oliveira, Paula Regina de [UNESP] (2014)
Agricultural practices and the modernization of agriculture are related to the use of intensive use of soil and machines, thus, the soil management, which aims to less degradation and more sustainable agriculture, have been sought by researchers, such as farmers. The objective of this study was to evaluate the physical quality of a typical Oxisol, through soil parameters and comparing the effect of four functions of pedotransfer for the curve of resistance to penetration, by tuning data obtained with penetrometer electronic management systems, no-tillage and conventional tillage, and evaluate the production of maize and soybeans. The experimental design was completely randomized split-plot (systems use x layers), in six replications. The treatments for maize were constituted by medium textured soil under no-tillage system, by 1; 8 and 10 consecutive years, and under conventional tillage, and the clay soil under no-tillage for 12 consecutive years, and under conventional tillage. Treatments for soybean were made by medium textured soil under no-tillage system, by 2; 9 and 11 consecutive years, and under conventional tillage and the clay soil under no-tillage, for 1 and 13 consecutive years, and under conventional tillage. The no tillage than 12 years, had lower production due to the formation of compacted layers, especially near the soil surface. The conventional tillage in clay soil under soybean had higher macroporosity and total porosity and lower density, whose production was higher, however, didn´t differ in no-tillage systems under two and nine years, and the other treatments didn´t have difference. In the soil of medium texture Equations RP = aUgb; RP = a (1-Ug)b; AebUg and RP = a + be-Ug/c showed similar precision and accuracy in predicting resistance to penetration. In the clayey soil Equations RP = a (1-Ug)b; RP = aebUg showed better performance